THE EU AND THE CURIOUS CASE OF THE COPENHAGEN ACCORD - Sabina Nicoleta Furtună (CES Working Papers, 2010)
The goal of the 2009 UN Climate Change Conference, commonly known as the Copenhagen Summit, has been to reach a legally binding agreement between participant states. As a successor to the Kyoto Protocol, this sort of agreement would have engaged signatory parties with reducing their greenhouse gas emissions in order to prevent the rise with 2 degrees Celsius in global temperature. This paper is an analysis of the above-mentioned event, which focuses on itsmain result, namely the Copenhagen Accord. It also presents the role of the European Union at the Copenhagen Summit and in promoting sustainable development globally.